Peran Unit Dikyasa Melalui Program Police Goes To School Terhadap Pelajar SMA Dalam Mengurangi Kecelakaan Lalu Lintas Di Polres Bogor - Hermawan, Bobby Patriatama (Indonesian Journal of Police Studies, 2020)
The high number of traffic accident involving students, especially high school students in Bogor districts is the problem that must be ancipated by the Bogor Police Traffic Unit. The problem occured because of the students’ lack of kno1wledge and awareness about traffic. Thus, the Bogor Police Traffic Unit assumes a job in giving state-funded public training through the POLICE GOES TO SCHOOL program to high school students in Bogor Regency. The purpose of the research in this thesis is to obtain an overview of the implementation of the program of public education provided by the Bogor Police Traffic Unit for students, and to identify the factors that influence the implementation of the program given by the Traffic Unit for high school students in Polres Bogor, and to probe deeper into what has been done and given by the Traffic Unit to high school students in the Bogor District Police through the community education program by the Dikyasa Unit. The concepts and theories that the writer use are the concept of Traffic Accidents, the concept of Dikmas Lantas from the National Police Chief (Kapolri) Implementation Guideline No.Pol: Juklak/5/V/2003 dated May 29, 2003 concerning guidelines for the Implementation of Community Education in the Field of Traffic (Dikmas Lantas), Theories and concepts of Management by G.R. Terry, and Motivation Theory. Also, in conducting research, the writer use qualitative research techniques from Prof. Dr. Sugiyono. The research was conducted using a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The data analysis technique used for the research is data triangulation, which was conducted in February 2020 at the Bogor District Police Station. From the research results obtained is the role of the Bogor District Police Dikyasa Unit in providing public education to high school students through a program that has been made known as POLICE GOES TO SCHOOL is conducted in accordance with the guidelines of the National Police Chief No.Pol: Juklak/5/V/2003 on 29 May 2003 on community education then, but in it’s implementation there are obstacles that exist in the Traffic Unit and the students themselves. Also, the number of unit members are not proportional to the size of Bogor Regency, not to mention, they do not have any experience in participating in the Traffic Development Education Program, specifically to provide public education.